2018
DOI: 10.1089/sur.2017.220
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes Has Low Susceptibility to Chlorhexidine Digluconate

Abstract: Different skin bacteria have different susceptibilities to disinfectants. To prevent SSIs, the selected disinfectant agent and the disinfection time should have bactericidal activity toward all the bacteria that pose a risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Hagi et al reported that bactericidal activity of olanexidine gluconate against various bacterial species was compared to CHG and PI by determination of minimum bactericidal concentration. 9) They used 100 species including Enterococcus faecalis, VRE, Staphylococcus aureus, MRSA, Staphylococcus epidermidis, Streptococcus pyogenes, Cutibacterium acnes, Acinetobacter baumannii, Burkholderia cepacia, Citrobacter freundii, Enterobacter cloacae, Escherichia coli, Proteus mirabilis, Proteus hauseri, Pseudomonas aeruginosa, Salmonella Typhimurium, Serratia marcescens, Stenotrophomonas maltophilia, and Bacteroides fragilis, which were also used in this study. The data showed that olanexidine gluconate had high bactericidal activity as well or better than CHG and PI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hagi et al reported that bactericidal activity of olanexidine gluconate against various bacterial species was compared to CHG and PI by determination of minimum bactericidal concentration. 9) They used 100 species including Enterococcus faecalis, VRE, Staphylococcus aureus, MRSA, Staphylococcus epidermidis, Streptococcus pyogenes, Cutibacterium acnes, Acinetobacter baumannii, Burkholderia cepacia, Citrobacter freundii, Enterobacter cloacae, Escherichia coli, Proteus mirabilis, Proteus hauseri, Pseudomonas aeruginosa, Salmonella Typhimurium, Serratia marcescens, Stenotrophomonas maltophilia, and Bacteroides fragilis, which were also used in this study. The data showed that olanexidine gluconate had high bactericidal activity as well or better than CHG and PI.…”
Section: Resultsmentioning
confidence: 99%
“…Olanexidine gluconate exerts strong and fastacting bactericidal activity against wide range of bacteria. 9) The bactericidal mechanism has been reported to occur via an interaction with the bacterial surface molecules, such as lipopolysaccharide and lipoteichoic acid, which subsequently disrupts cell membranes and degrades proteins. 9) Therefore, the bactericidal effect of olanexidine gluconate is irreversible owing to the loss of intracellular components.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that some C. acnes isolates required a higher chlorhexidine digluconate MBCs (minimum bactericidal concentrations) than the concentration used in commercial preparations (2%). On the other hand, MBCs determined in the same study for iodine-povidone, ethanol, and benzalkonium chloride were lower than their commercial concentrations [ 116 ].…”
Section: Skin Disinfection and Its Influence On The Microbiome Comentioning
confidence: 99%
“…Ultimately, 79 studies (33)(34)(35)(36)(37) 96)) and povidone-iodine (37,46,49,70,76,91). In total, MBC data from 6218 microbes were extracted.…”
Section: Resultsmentioning
confidence: 99%
“…Articles were published between 1976 and 2021, although the majority (95%) were published this century. The antiseptics used included five different CHX salts (digluconate (33,35,37,40,47,50,(55)(56)(57)(58)61,63,67,69,74,75,81,83,88,90,94,97,99,101,106,107,111,113), gluconate (34,36,42,42,53,91,102,103,108,108,109,112), dichlorohydrate (85)(86)(87), diacetate (71,99) and dihydrochloride( 96)) and povidone-iodine (37,46,49,…”
Section: Study Characteristicsmentioning
confidence: 99%